(3EjVGM GdOQI GdeVjI aj bQGAGJ GdKdGKI GdUMjMI GdeQVjIs - (3YKeGf Hf YeQ Hf CHj HcQ GdfGTQj, Yaja GdOjf , J (B848 (3g`s; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Jhdi MaX cJGHg Gdecfhf , abGd(B: (3EfG fMf fRdfG GdPcQ hEfG dg dMGaXhf hbGd JYGdi aj GdbQBf GdeLjO(B: (3dG jCJjg GdHGWd s
(3BNQgG (B:s
(3hQGbHJ faSj cd Mjf hdMXI hdGbjJ QHj dGYdi hdGdjG Je EjVGM GdOQI s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdOQI GdeVjI fXegG GdLRQi cedI GdTGWHjI Ydi hRfgG hQhjJgGs
(3GdfSNI HgG MhGTs
(3Ydi gGeTgG JYdjbGJ hebGHdIs
(3hocJHJ GdYfGhjf HGdMeQI s
(3jdjg cJGH cfR GdeYGfj aj TQM MQR GdCeGfj s
(3bQf GdfSN (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs